2021
DOI: 10.3390/life11040313
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Overweight/Obesity and Executive Control in College Students: The Mediating Effect of BDNF and 5-HT

Abstract: The main aim of this study was to explore the association between overweight/obesity and executive control (EC) in young adults, and to further analyze the mediating effect of brain-derived neurotrophic factor (BDNF) and serotonin (5-hydroxytryptamine (5-HT)) on the relationship between overweight/obesity and EC. A total of 449 college students aged between 18 and 20 years were recruited for the study between March and December 2019. Their height and weight were then measured professionally. Subsequently, body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…The results of the analysis showed that there was a negative correlation between serum BDNF levels and BMI and WHR (Figure 1). These results are in line with the results of a study conducted by Si et al [32] that there is a negative correlation between BMI and BDNF levels in male and female students. A study conducted by Yang et al [33] also reported that BDNF levels have a significant correlation with BMI in female.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of the analysis showed that there was a negative correlation between serum BDNF levels and BMI and WHR (Figure 1). These results are in line with the results of a study conducted by Si et al [32] that there is a negative correlation between BMI and BDNF levels in male and female students. A study conducted by Yang et al [33] also reported that BDNF levels have a significant correlation with BMI in female.…”
Section: Discussionsupporting
confidence: 93%
“…Having proven by the results of a study by Lee et al [40], the baseline BDNF levels in individuals with obesity are lower than that of in the individuals without obesity. Furthermore, a study conducted by Si et al [32] reported that was associated with the decrease in BDNF levels in adolescents aged 18-20 years. Obesity can reduce serum neurotrophic factor levels and cause blood-brain barrier (BBB) dysfunction [41].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present study, three core EFs (inhibition, working memory, and cognitive flexibility) were tested on the computer by a test tool developed by Chen et al (37), which has been used in many previous studies (38)(39)(40)(41). A modified Eriksen flanker task was used to assess the inhibition aspect of EF (42), and the response times (RT, ms) in the congruent and incongruent trials were recorded as result.…”
Section: Executive Functionmentioning
confidence: 99%